Journey and evolution of the English alphabet. - Wong, Jasmine Shu Ting. (2011)
“In the beginning was the Word, and the Word was with God, and the Word was God.” John 1:1 God created Man on the sixth day to rule over the animals and creatures He created. Man had the advantage to do so, as we were given the gift of speech. As time goes by, our intelligence progressed as well, and soon, we realized that the capacity of the mind was not enough to store all the information needed. Hence we started to pen down our thoughts by making marks in a form of pictures and complicated symbols. Humans continued to progress in life and we soon realized that we needed more than what was available around us to survive, be it food, or materials to keep warm. This was when people from different regions started to barter trade with each other. In order for each party to honour their side of the trade, we came up with written agreements to prevent any party from backing out through the deal. More and more new symbols everyday were drawn. It became difficult to keep up with the new additions. Hence, alphabet systems were created from different regions of the globe.